2008
DOI: 10.1128/mcb.01469-07
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Activation of Multiple Dimeric Transcription Factors within the NF-κB Signaling System

Abstract: The NF-B signaling pathway regulates the activity of multiple dimeric transcription factors that are generated from five distinct monomers. The availabilities of specific dimers are regulated during cell differentiation and organ development and determine the cell's responsiveness to inflammatory or developmental signals. An altered dimer distribution is a hallmark of many chronic diseases. Here, we reveal that the cellular processes that generate different NF-B dimers are highly connected through multiple cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 45 publications
(90 reference statements)
9
155
0
2
Order By: Relevance
“…Interestingly, nfkb1 -/-mice were also shown to have inguinal lymph node defects and derived MEF showed attenuated RelB activation in response to LTβR stimulation (Lo et al, 2006). As described earlier, rela -/-mice also exhibited an early organogenic defect with complete absence of lymph nodes in new born mice (Alcamo et al, 2002), and RelB:p52 dimer activation by LTβR signaling was shown to be defective in rela -/-MEF (Basak et al, 2008). As opposed to the commonly held view of distinct canonical and non-canonical signaling axes, these studies indicated the potential involvement of multiple cross-regulatory mechanisms, whose details may best be presented and characterized within network description of the NF-κB signaling system.…”
Section: Disparate Lymph Node Phenotype In Various Nf-κb Knockoutssupporting
confidence: 54%
See 4 more Smart Citations
“…Interestingly, nfkb1 -/-mice were also shown to have inguinal lymph node defects and derived MEF showed attenuated RelB activation in response to LTβR stimulation (Lo et al, 2006). As described earlier, rela -/-mice also exhibited an early organogenic defect with complete absence of lymph nodes in new born mice (Alcamo et al, 2002), and RelB:p52 dimer activation by LTβR signaling was shown to be defective in rela -/-MEF (Basak et al, 2008). As opposed to the commonly held view of distinct canonical and non-canonical signaling axes, these studies indicated the potential involvement of multiple cross-regulatory mechanisms, whose details may best be presented and characterized within network description of the NF-κB signaling system.…”
Section: Disparate Lymph Node Phenotype In Various Nf-κb Knockoutssupporting
confidence: 54%
“…LTβR stimulation was shown to induce nuclear accumulation of RelB:p52 via the NIK/IKK1 pathway and the phosphorylation and processing of de novo synthesized, rather than preexisting p100 protein (Mordmuller et al, 2003;Senftleben et al, 2001;Xiao et al, 2001). Indeed, a first phase of RelA activity was proposed to induce p100 synthesis to amplify RelB:p52 dimer activation (Dejardin et al, 2002;Muller and Siebenlist, 2003), but recent evidence indicates that RelA-responsive expression of RelB is more important in this regard (Basak et al, 2008). Signaling through multiple other TNF receptor superfamily members, such as BAFFR, CD40R, BCMA, TAC1 or RANK, was also reported to activate the RelB:p52 dimer via the non-canonical pathway.…”
Section: Non-canonical Activation Of Nf-κb/relb Dna Binding Acitvitymentioning
confidence: 99%
See 3 more Smart Citations